Diasporic Participation In Homeland Democratic Processes: Democracy Beyond Border In The Internet Era - Muhammad Abdullahi Maigari; Kamselem Shehu (Journal of Religion, Local Politics, and Law, 2025)
In many developing democracies, prior to the internet and social media, people living abroad had limited opportunities to engage in their home countries' democratic processes. Existing literature mostly addresses remittances, economic impacts, immigration laws, and the challenges faced by migrants. This paper reassesses the political contributions of the diaspora to the democratic development of their home countries.It explored how technology, particularly the Internet, aided the diaspora in sending uncensored messages to their home countries during electioneering campaigns and voting in countries. Despite being legally barred from voting while abroad, citizens in the diaspora use social media to influence elections and political opinions in their home countries. This paper highlights how diaspora engagement through social media shaped voting behavior and affected election outcomes in Nigeria and other nations between 2019 and 2024. Unfortunately, many developing democracies still do not allow their citizens living abroad to vote, limiting their participation despite their significant contributions.